1978
DOI: 10.1071/bi9780601
|View full text |Cite
|
Sign up to set email alerts
|

The Administration of Flumethasone, by Three Different Routes, its Measurement in the Plasma and Some Effects on Wool Growth in Merino Wethers

Abstract: Flumethasone was given to Merino wethers weighing 30-50 kg at rates of 0·62-1· 35 mg/kgO' 7 5 by intravenous (experiments 1 and 2), intraruminal (experiment 4) and subcutaneous (experiment 5) routes over 8 days. In experiment 3, 1· 2 mgflumethasone/kg'"?" was given intravenously over 4, 5 or 6 days. The plasma concentration profiles showed concentrations in the order: intravenous > subcutaneous > intraruminal. Plasma concentration patterns usually were highest during the first 48 h of infusion followed by rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

1978
1978
2003
2003

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…The effects of dexamethasone on wool fibre shedding were classified in a similar way to that used by Panaretto and Wallace (1978b). Briefly a shed wool fibre was defined as one that lay outside the fibre canal.…”
Section: Effects Of Dexamethasone On Fibre Sheddingmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of dexamethasone on wool fibre shedding were classified in a similar way to that used by Panaretto and Wallace (1978b). Briefly a shed wool fibre was defined as one that lay outside the fibre canal.…”
Section: Effects Of Dexamethasone On Fibre Sheddingmentioning
confidence: 99%
“…Subsequently it has been found that the slow intravenous infusion of glucocorticoid analogues over an 8-day period caused wool shedding in a greater proportion of the total fibres than when the same dose was infused over a shorter period (Panaretto and Wallace 1978b).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of wool growth after treatment is also variable and occasionally persists for long periods. An earlier study dealt with wool growth and plasma steroid concentrations following the injection of synthetic glucocorticoids by different routes (Panaretto and Wallace 1978b). However, no comparisons have been made when animals are treated by the same route with different forms of a particular steroid.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of several glucocorticoids to sheep and the resultant inhibition of growth of wool fibres have been well documented (Panaretto and Wallace 1978a, 1978b, 1979Leish and Panaretto 1978). In ,order to induce shedding of the majority of wool fibres, it was found necessary to maintain elevated glucocorticoid concentrations in the plasma of sheep over 8 days or longer (Panaretto 1979).…”
Section: Introductionmentioning
confidence: 99%